The Darjeeling Limited - Anderson, Wes 1969-; Rudin, Scott 1958; Coppola, Roman; Pilcher, Lydia Dean; Schwartzman, Jason 1980-; Wilson, Owen 1968-; Brody, Adrien (Fox Searchlight Pictures, 2007)
Having not spoken to each other in a year, three American brothers set off on a train voyage across India with a plan to find themselves, bond, and regain their friendship with each other. Their spiritual quest, however, veers rapidly off-course -- thanks in part to over-the-counter pain killers, Indian cough syrup, and pepper spray. Eventually the three find themselves stranded alone in the desert with eleven suitcases, a printer, and a laminating machine. From this point forward, an unplanned journey begins.